Talking about sex after traumatic brain injury: perceptions and experiences of multidisciplinary rehabilitation professionals - Dyer, Kerry; das Nair, Roshan (Taylor & Francis, 2013)
Purpose: Research indicates that although 50–60% of people who have had a traumatic brain injury (TBI) experience changes in sexual functioning, sexuality issues remain largely unaddressed in rehabilitation. This study aimed to explore rehabilitation professionals’ perceptions and experiences of discussing sexuality with service-users who have had a TBI.